Benefits of a good posture in Cello playing the relation between posture and quality of performance / Mohd Iqbal Mohd Hisham - Mohd Hisham, Mohd Iqbal (2011)
This study was carried out to addressed the benefits of posture in cello playing in relations between posture and quality of performance A total of five (5) respondents was selected to be interviewed during the period given of the study. A set of interview was designed and conducted to gain primary data from the respondents. A non-participant observation was also selected to be one of the data collection method in this study. From the overall findings, the study showed that there was two benefits gained by an appropriates posture in cello playing related towards the posture and the quality of performance. The study also carried out the causes that prevent cellists from executing the right posture while playing and the effects when cellists neglecting the right posture‘ In conclusion, the study the benefits towards posture in cello playing was addressed. Hence, recommendation for further research is included in this study.